2019
DOI: 10.1136/bmjopen-2019-029544
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed foods and recommended intake levels of nutrients linked to non-communicable diseases in Australia: evidence from a nationally representative cross-sectional study

Abstract: ObjectiveThis study aimed to describe the consumption of ultra-processed foods in Australia and its association with the intake of nutrients linked to non-communicable diseases (NCDs).DesignCross-sectional study.SettingNational Nutrition and Physical Activity Survey (2011-2012).Participants12,153 participants aged 2+ years.Main outcome measuresAverage dietary content of nutrients linked to NCDs and the prevalence of intake outside levels recommended for the prevention of NCDs.Data analysisFood items were class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
184
6
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(227 citation statements)
references
References 51 publications
20
184
6
17
Order By: Relevance
“…Fifteen percentage of animal energy content may appear small at first view, but it is sufficient to supply all the essential macro-and micronutrients, provided the third rule (varied) is correctly applied (Tables 5 and 6). In addition, a reduction in ultra-processed energy content ('empty' energy content) will bring in new, minimally processed nutrient-dense foods rich in bioactive compounds that are protective against chronic diseases (i.e., more fibre, vitamins, minerals and antioxidants) (46)(47)(48)(49)(50)(51)96,97) . Notably, iodine and vitamin A DRI are easier to address when including a weekly serving of seaweeds/seafood (e.g., dried seaweeds) and offal/giblets (e.g., animal liver), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen percentage of animal energy content may appear small at first view, but it is sufficient to supply all the essential macro-and micronutrients, provided the third rule (varied) is correctly applied (Tables 5 and 6). In addition, a reduction in ultra-processed energy content ('empty' energy content) will bring in new, minimally processed nutrient-dense foods rich in bioactive compounds that are protective against chronic diseases (i.e., more fibre, vitamins, minerals and antioxidants) (46)(47)(48)(49)(50)(51)96,97) . Notably, iodine and vitamin A DRI are easier to address when including a weekly serving of seaweeds/seafood (e.g., dried seaweeds) and offal/giblets (e.g., animal liver), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed a trend in the last decades toward a decrease in the consumption of fresh food (mainly vegetables and fruits) in favor of ultra-processed foods ( 247 ) and how this change correlates with the increase in obesity prevalence worldwide. Other studies have correlated the consumption of ultra-processed foods with the increase in sugars, saturated and trans-fat, and Na intake, that in addition, correlate with an associated higher energy intake and obesity prevalence ( 248 251 ). In relation to the increase in cancer incidence associated with MetS, Fiolet et al found that a 10% increase in the proportion of ultra-processed foods in the diet was associated with a significant increase (>10%) in the risk of overall cancer and more specifically of postmenopausal breast cancer, the most commonly related to obesity ( 237 ).…”
Section: Metabolic Syndrome: Definitionmentioning
confidence: 99%
“…First, unfavorable nutritional composition of ultra-processed foods may be a key factor driving the observed associations. It has been found that ultra-processed food consumption is positively associated with added sugar intake and inversely associated with dietary ber intake [36], both of which are shown to be predictive of cardiovascular mortality [37,38]. Second, chemicals may transfer from packaging materials to food contents, some of which may have detrimental impacts on cardiometabolic health [39].…”
Section: Interpretation and Comparison With Other Studiesmentioning
confidence: 99%